Proposal for changing the item of work for water treatment plant system - BUCG-ABC Joint Venture (Brac University, 2023)
This variation order has been made between Brac University and BUCG-ABC joint venture for Proposal for changing the item of work for water treatment plant system of Brac University new campus project.